2018
DOI: 10.3390/ijgi7020071
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Footprints of Human Perceptual Experience in Geo-Social Media

Abstract: Analyses of social media have increased in importance for understanding human behaviors, interests, and opinions. Business intelligence based on social media can reduce the costs of managing customer trend complexities. This paper focuses on analyzing sensation information representing human perceptual experiences in social media through the five senses: sight, hearing, touch, smell, and taste. First a measurement is defined to estimate social sensation intensities, and subsequently sensation characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…It can be considered as a crucial feature to discriminate a text in terms of human sensation. In the recent work (Lee, Ogawa, Kwon, & Kim, 2018), a dedicated measure was proposed for estimating the sensation intensity. In particular, the authors identified meaningful regional differences of sensation intensity depending on a native language and temperature.…”
Section: Measurement Of Sensation Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be considered as a crucial feature to discriminate a text in terms of human sensation. In the recent work (Lee, Ogawa, Kwon, & Kim, 2018), a dedicated measure was proposed for estimating the sensation intensity. In particular, the authors identified meaningful regional differences of sensation intensity depending on a native language and temperature.…”
Section: Measurement Of Sensation Classificationmentioning
confidence: 99%
“…(Lee, Thabsuwan, Pongpaichet, & Kim, 2018) improved that method taking into account a lexical semantic relation of words based on Wordnet (Miller, 1995) graph structure. Accordingly, we adopt those measures of sensation intensity as a feature for the sensation classification: Sensation Intensity (Lee, Ogawa, et al, 2018) …”
Section: Measurement Of Sensation Classificationmentioning
confidence: 99%